THE USING OF “IJIN” AS THE POLITENESS STRATEGIES ON PHATIC COMMUNION IN STIMART AMNI SEMARANG - Aprillina Aprillina (JURNAL SAINS DAN TEKNOLOGI MARITIM, 2011)
This study was conducted to know the using of “ijin” as the politeness strategies on phatic communion in stimart amni semarang in case for the students in the maritime field. This study mainly discuss about the politeness theory which is applied on phatic communion in STIMART AMNI students. The interview has been selected as the instruments to study what kinds of phatic communion in students of STIMART AMNI Semarang in deal with the using of “ijin” and to what extend the using of “ijin” of the STIMART AMNI Semarang’s students in deal with its response. It involves student’s activities in their interaction. There are some principles that should be followed so that the utterances become polite. Those are : asking permission, showing politeness, and make sombodyelse feel comfortable, and be friendly which based on regular verbal rule. Students in the lower level might use “ijin” as a strategy of showing positive politeness. The students in higher levels do not use the same expression to show their response of positive politeness in order to discover the best implementation of the communication aims. Keywords: Pragmatic theory, politeness, Phatic communion